Universalism of Islamic Scholarly Tradition: New Directions for Islamic Studies - Siregar, Ibrahim; Rangkuti, Suheri Sahputra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
AbstractThe universalism of the Islamic scholarly tradition is seen as one of the keys in responding to some challenges and opportunities that come along with an increasingly connected modernity. This research examines the evolution of Islamic thought from a period of disintegration to integration and underscores the importance of the universalist approach in uniting different schools and views within the Islamic world. The type of research used in this study is library research using a paradigmatic philosophical-historical analysis approach. The research combines three approaches: philosophical, historical, and paradigmatic analysis. In this context, philosophical analysis explores concepts related to universalism in Islam. The data in this research were obtained through a literature study. Researchers are involved in in-depth reading several books, papers, articles, and classical texts relevant to the past understandings of universalism. These data are also used for perspective enrichment. The results of this study show the originality of tradition and modernity as historical roots and a foothold departing from the discussion of universalism of the Islamic scientific tradition. In addition, the results of this study also emphasize three methods of approach to produce universalism of the scientific tradition, namely: ideological criticism, historical analysis, and structural analysis.Â Universalisme tradisi keilmuan Islam dipandang sebagai salah satu kunci untuk menanggapi tantangan dan peluang yang datang bersama dengan modernitas yang semakin terhubung. Penelitian ini membahas tentang evolusi pemikiran Islam dari periode disintegrasi ke integrasi dan menggarisbawahi pentingnya pendekatan universalisme dalam menyatukan berbagai aliran dan pandangan di dunia Islam. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kepustakaan (library research) dengan menggunakan pendekatan analisis filosofis-historis paradigmatik. Penelitian ini menggabungkan tiga pendekatan: analisis filosofis, historis, dan paradigmatik. Dalam konteks ini, ketiga pendekatan tersebut dipergunakan untuk mengeksplorasi konsep-konsep yang berkaitan dengan universalisme dalam Islam. Data dalam penelitian ini diperoleh melalui studi pustaka, yang melibatkan pengumpulan buku, makalah, artikel, dan teks klasik yang relevan dengan topik penelitian yang mencerminkan pemahaman masa lalu tentang universalisme, juga digunakan untuk pengayaan perspektif. Hasil penelitian ini menunjukkan orisinalitas tradisi dan modernitas sebagai akar sejarah dan pijakan berangkat dari pembahasan universalisme tradisi ilmiah Islam. Selain itu, hasil penelitian ini juga menekankan tiga metode pendekatan untuk menghasilkan universalisme tradisi ilmiah, yaitu: kritik ideologis, analisis sejarah, dan analisis struktural.